2022
DOI: 10.1080/07853890.2022.2104920
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in esophageal variceal bleeding in the United States

Abstract: Background and Aims Esophageal variceal bleeding is a common reason for hospitalization in patients with cirrhosis. The main objective of this study was to analyze the effects of gender differences on outcomes in hospitalizations related to Esophageal variceal bleeding in the United States. Methods A retrospective observational cohort study was performed using the National Inpatient Sample (NIS) database for all hospitalizations with a discharge diagnosis of esophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Other studies have suggested that males typically have worse in-hospital outcomes than females with variceal bleeding. 19 Our study may not have been able to see the same result given the significant proportion of female patients in the VB group.…”
Section: Discussionmentioning
confidence: 62%
“…Other studies have suggested that males typically have worse in-hospital outcomes than females with variceal bleeding. 19 Our study may not have been able to see the same result given the significant proportion of female patients in the VB group.…”
Section: Discussionmentioning
confidence: 62%
“…However, the difference between the two groups is insignificant. To explain the gender finding in the control group, the typical history of liver disease showed that 55% and 70% of all cases were in men (Sohal et al, 2022). From the researchers' point of view, half of the study group consisted of female patients because female patients may develop liver cirrhosis later than males related to the protective activity of estrogen (Lee et al,…”
Section: Resultsmentioning
confidence: 99%
“…This rise is caused by scar tissue or a clot restricting the liver's normal blood supply. Varices form when blood bypasses the larger vessels and flows through the small vessels in the esophagus (Sohal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The database has been described in detail previously. 24 , 25 , 26 Since the data obtained is publicly available de‐identified data, IRB approval was not required.…”
Section: Methodsmentioning
confidence: 99%